The changing nature of jobs in Central and Eastern Europe - Piotr Lewandowski (IZA World of Labor, 2017)
Job polarization can pose serious problems for emerging economies that rely on worker reallocation from low-skilled to middle-skilled jobs to converge toward advanced economies. Evidence from Central and Eastern European (CEE) countries shows that structural change and education expansion can prevent polarization, as they enable a shift from manual to cognitive work and prevent the “hollowing out” of middle-skilled jobs. However, in CEE countries they have also led to a high routine cognitive content of jobs, which makes such jobs susceptible to automation and computerization in the future.
Keywords: J21; J23; J24; 330; restructuring; workforce upskilling; task content of jobs